Inactivation of myostatin by photo-oxygenation using catalyst-functionalized peptides. Issue 62 (12th July 2019) - Okamoto, Hideyuki; Taniguchi, Atsuhiko; Usami, Shoya; Taguchi, Akihiro; Takayama, Kentaro; Hayashi, Yoshio
Abstract : A myostatin-binding peptide which is functionalized by equipped with on/off switchable photo-oxygenation catalyst drastically inactivates myostatin, leading to a new therapeutic strategy for amyotrophic diseases. Abstract : Inhibition of myostatin is an attractive treatment for muscular dystrophy and other amyotrophic diseases. A myostatin-binding peptide was functionalized by equipped with an on/off switchable photo-oxygenation catalyst. This peptide induces a selective oxygenation of myostatin under near-infrared light, resulting in inactivation of myostatin. This peptide shows several orders of magnitude greater inhibitory effect than the original peptide.